(untitled) (Journal of Applied Membrane Science & Technology, 2022)
Surface contamination with pathogenic microorganisms such as E. coli and S. aureus may lead to the spread of numerous diseases such as pneumonia and sepsis. The most common sources of surface contamination are human contamination and the environment, which includes air, dust, and water. Conventional cleaning and disinfection practices are not sufficient to ensure the safety and not environmentally friendly to use. It has been proposed that a visible light active photocatalytic antimicrobial coating on the indoor surface can successfully control this increasing threat. Photocatalysis is recognized as one of the promising approaches and metal oxides as photocatalyst have showed significant potential antibacterial agents against a variety of bacteria. Cuprous oxide (Cu2O) has been recognized as potential visible light active photocatalyst for antimicrobial applications due to its large bandgap. The current review highlights the antimicrobial properties of various Cu2O-based photocatalyst and their potential use as coatings. This review article will introduce the related parameters in Cu2O-based photocatalyst applications as antimicrobial coatings in order to provide better understanding on achieving excellent performance in photocatalytic disinfection. This review may be beneficial in guiding photocatalyst research for antimicrobial applications in the visible light region.